Should eye protection be worn during dermatological surgery: prospective observational study - Birnie, A.J.; Thomas, K.S.; Varma, Sandeep (Wiley, 2007)
Background There is a potential risk of infection with blood-borne viruses if a doctor receives a blood splash to a mucous membrane. The quantification of facial contamination with blood has never been documented in the context of dermatological surgery. Objectives (i) To identify the number of facial blood splashes that occur during skin surgery and to identify the procedures that present higher risks for the operator and assistant. (ii) To assess the provision of eye protection and attitudes to its use in dermatological surgery in the U.K. Methods (i) Prospective, observational study in the skin surgery suite of a U.K. teaching hospital assessing 100 consecutive dermatological surgery procedures, plus 100 consecutive operations in which an assistant was present. Primary outcome: number of face-mask visors with at least one blood splash. Secondary outcomes: to identify if any of the following variables influenced the occurrence of a blood splash: grade of operator, site and type of procedure, and the use of electrocautery. (ii) A postal survey of all U.K.-based members of the British Society of Dermatological Surgery (BSDS) was conducted assessing facilities available and the attitudes of U.K.-based clinicians to the use of face masks during surgery. Results (i) In 33% of all surgical procedures there was at least one facial splash to the operator (range 1–75) and in 15% of procedures the assistant received at least one splash (range 1–11). Use of monopolar electrocautery was significantly less likely to result in splashes to the mask compared with bipolar electrocautery [odds ratio (OR) 0Æ04; 95% confidence interval (CI) 0Æ01–0Æ19]. Compared with the head/neck, operations on the body were significantly more likely to result in splashes to the mask (OR 6Æ52) (95% CI 1Æ7–25Æ07). The type of procedure and the status of the operator did not have a bearing on the likelihood of receiving a splash to the mask. (ii) From the survey, 33 of 159 (20Æ8%) of BSDS members had no face masks available and 54 of 159 (34Æ0%) did not wear any facial protection while operating. The majority (53Æ5%) thought they received a splash in £ 1% of procedures. Conclusions There is a substantial risk of a splash of blood coming into contact with the face during dermatological surgery for both the operator and assistant, regardless of the procedure. The risk of receiving a blood splash to the face may be substantially underestimated by U.K.-based dermatologists. The use of protective eyewear is advisable at all times, but particularly when using bipolar electrocautery, or when operating on high-risk individuals.